Treatment algorithm for chronic vertebrogenic back pain: the role of chondroprotectors - O. S. Levin; E. E. Vasenina; A. I. Nebozhin; A. Yu. Nikitina (Klinicist)
Back pain constitutes one of the major medico-social problems of healthcare. The development of a unified approach to the diagnosis and treatment of back pain is hindered since it is difficult to assess the various approaches to its treatment, especially its chronic forms. Yet recent data witnessing the important role of the neuroinflammatory process in the pathogenesis of the degenerative forms of discopathy suggest that the traditional treatment approach, which includes physical therapy exercises and non-steroidal anti-inflammatory drugs and myorelaxants, could be enhanced by using drugs characterized by slow structure-modifying action on the structure of the cartilaginous tissue of intervertebral discs and joints. Given the intelligent use of manual therapy, needle reflex therapy, kinesiotherapy, as well as modification of psychosocial factors that pre-determine the yellow flag phenomenon, the application of sustained-release symptomatic drugs increases the efficacy of therapy and prevents subsequent pain episodes. As of today, a placebo-controlled study has proven the action of Alflutop, which can be administered both intramuscularly and paravertebrally. This approach not only improves the patients’ condition but also reduces the burden associated with chronic back pain problems for the society.